A Nonarchetypal 5, 6‐Dihydro‐2H‐pyrano[3, 2‐g]indolizine‐Based Solution‐Solid Dual Emissive AIEgen with Multicolor Tunability. Issue 19 (15th March 2017) - Raghuvanshi, Ashutosh; Jha, Ajay Kumar; Sharma, Ashutosh; Umar, Shahida; Mishra, Shachi; Kant, Ruchir; Goel, Atul
Abstract: Screening of a chemical library of pyranones and their ring transformed fluorophores led to the discovery of a novel 5, 6‐dihydro‐2 H ‐pyrano[3, 2‐ g ]indolizine (DPI ) class of the luminogenDPI 7, which exhibited unique solution–solid dual emission (SSDE) behavior with an emission color shift from bright‐green in solution to a strong red emission in the solid state. The AIE mechanism of these luminogens revealed a well‐defined set of noncovalent interactions (CH⋅⋅⋅O and CH⋅⋅⋅N) that block the motion of C2 ‐flexure leading to restriction of intramolecular vibrations (RIV) in the solid state.DPI ‐7 is the first example of solution–solid dual emissive RIV‐based AIEgen, which has great potential both in biomedical imaging and optoelectronic fields. Abstract : Multicolor AIEgens : A novel dihydropyranoindolizine class of compounds as restriction of intramolecular vibration (RIV)‐based aggregation‐induced emission agents (AIEgens) with strong fluorescence in the solid state was discovered. The donor–acceptor modulations in the core led to multicolor AIEgens. One of these (DPI‐7 ) exhibited solution–solid dual emissive (SSDE) behavior that may be applicable to material and biological sciences.